The Code.org platform in the developing of computational thinking with elementary school students - Barradas, Rolando (2021)
Computational thinking is the thinking process involved in formulating problems to admit a computational solution. This article describes a study in which the code.org platform was used to develop computational thinking with Elementary school students. After proper introduction and contextualization, we describe the 198 students from 4th grade involved in the study, following the process of collecting and analyzing data from the code.org platform. We conclude with the evaluation carried out by the students. The main conclusion of this study is that code.org is a valid option for developing computational thinking with Elementary school students. Also, a reliable way for students to start solving real-life problems, stimulating the capacity for abstraction through simulated and experienced practice.